An environmentally-benign NaNbO3 based perovskite antiferroelectric alternative to traditional lead-based counterparts. Issue 48 (29th November 2019) - Xie, Aiwen; Qi, He; Zuo, Ruzhong; Tian, Ao; Chen, Jun; Zhang, Shujun
Abstract : NaNbO3 -based lead-free AFE R-phase ceramics with Pnma space group and nanoscale stripe domain exhibit completely reversible field induced AFE–FE phase transition, featuring a relatively low E A–F of ∼8 kV mm −1 and a large repeatable strain of ∼0.29%. Abstract : Perovskite-structured antiferroelectric (AFE) materials, which are dominated by PbZrO3 based solid solutions, are of particular importance owing to their excellent electromechanical properties. The driving force for new development of AFE materials is the result of environmental regulations which require the exclusion of lead components. However, currently reported lead-free AFE materials either show inferior stability or need extremely high driving fields ( E A–F ) for AFE–FE phase transition. Here we report a new NaNbO3 -based solid solution with a room-temperature stable AFE phase and completely reversible field induced AFE–FE phase transition, possessing a relatively low E A–F of ∼8 kV mm −1, a large repeatable strain of ∼0.29%, and a large polarization difference ( P max ∼ 24 μC cm −2, P r ∼ 0 μC cm −2 ). The local and average structures were studied by transmission electron microscopy, in situ Raman spectrum and synchrotron X-ray diffraction, revealing that the solid solution with ≥16 mol% SrTiO3 belongs to the Pnma space group and exhibits nanoscale stripe domains of ∼55 nm, and reversibly responds to large external electric fields. This makes it a competitive lead-free AFE candidate for future applications of high-power energy-storage capacitors and large-displacement actuators.